2007
DOI: 10.7205/milmed.172.11.1170
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Based Instant Hand Sanitizer Use in Military Settings: A Prospective Cohort Study of Army Basic Trainees

Abstract: We investigated the impact of a customized alcohol-based instant hand sanitizer hand-hygiene regimen in an Army basic training setting. The entire population at the U.S. Army Field Artillery Training Center, Fort Sill, Oklahoma, participated in the 13-week prospective cohort study between January 18, 2005 and April 18, 2005. Two training battalions were randomly assigned to the control group, one to the primary intervention group (customized Purell Instant Hand Sanitizer regimen, education, reinforcement) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…A previous study conducted with military personnel, found that a Purell® instant hand sanitizer regimen helped to reduce healthcare encounters by 39% (p < 0.01), respiratory illness by 40% (p < 0.01), gastrointestinal illnesses by 48% (p < 0.02), and lost training time by 44% (p < 0.01) (Mott et al, 2007).…”
Section: Justificationmentioning
confidence: 93%
See 4 more Smart Citations
“…A previous study conducted with military personnel, found that a Purell® instant hand sanitizer regimen helped to reduce healthcare encounters by 39% (p < 0.01), respiratory illness by 40% (p < 0.01), gastrointestinal illnesses by 48% (p < 0.02), and lost training time by 44% (p < 0.01) (Mott et al, 2007).…”
Section: Justificationmentioning
confidence: 93%
“…This lack of hand hygiene has economic consequences for the military due to the increasing training time and the absentee rate among soldiers (Russell et al, 2006). The military has acknowledged the critical need to identify a costeffective method to prevent communicable diseases in the military population (Altman & Fechter, 1967;Mott et al, 2007;Riddle, Murray, Cash, Pimentel, & Porter, 2013;Russell et al, 2006). Ideally, a proactive approach to the prevention of communicable diseases would allow the military to recover a significant amount of training time while reducing outpatient physician visits and medical costs.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations